2015
DOI: 10.3329/updcj.v4i2.24041
|View full text |Cite
|
Sign up to set email alerts
|

Is there is any relationship between malocclusion and nutritional pattern of children

Abstract: Abstracts:Objective: Malnutrition of children results the underdevelopment of skeleton and facial structure, which might causes the malocclusion in developing dentitions. The study was aimed to investigate the relationship between the malocclusion and malnutrition. Method: Cross-sectional observational study was done with structured questioner from 627 school children (276 male, 349 female) of 7 to 15years age. Variable were set according to WHO guideline of malocclusion and malnutrition. Result: Among the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…2 Khan S. H. et al compared dental crowding with malnutrition and showed no significant relationship, describing that the subjects with the habit showed dental crowding but other subjects didn"t showed any significant relationship with malnutrition and malocclusion. 7 In the present study, there was significant association of dental caries with the salivary flow rate as compared to other individuals. Similar to this study, Moynihan P. et al described that the deficiency of PEM and vitamin A leads to affect the buffer capacity of the saliva which leads to dental caries 8 conducted similar study on nutrition with dental caries and stated the correlation between dental caries and nutrition of the patient that gave significant relationship.…”
Section: Discussionmentioning
confidence: 53%
“…2 Khan S. H. et al compared dental crowding with malnutrition and showed no significant relationship, describing that the subjects with the habit showed dental crowding but other subjects didn"t showed any significant relationship with malnutrition and malocclusion. 7 In the present study, there was significant association of dental caries with the salivary flow rate as compared to other individuals. Similar to this study, Moynihan P. et al described that the deficiency of PEM and vitamin A leads to affect the buffer capacity of the saliva which leads to dental caries 8 conducted similar study on nutrition with dental caries and stated the correlation between dental caries and nutrition of the patient that gave significant relationship.…”
Section: Discussionmentioning
confidence: 53%
“…Its accuracy in estimating dental arch widths has been supported by some studies [7,8]. In spite of the fact that some researchers, like Lohakare, have concluded that Pont's index should be used to predetermine ideal arch width values and applied clinically for patients undergoing orthodontic and other dental treatment [8], others have concluded that the index is not reliable enough to be used for clinical purposes [9][10][11][12] due to the fact that its dimension is affected by ethnicity [13], nutrition [14], systemic diseases [15], hormonal factors [16], and gender [17].…”
Section: Introductionmentioning
confidence: 99%
“…The erupting teeth that occur in an 8-year-old child are permanent maxillary lateral incisors; in a 9-year-old, they are permanent mandible canines, and in a 10-year-old, they are permanent maxillary and mandible first premolars, and also permanent maxillary second premolars. 3 Changes in the growth of the dentocraniofacial complex caused by poor nutrition can be reflected in the reduced space for tooth eruption 4 . Mack 1 states a significant relationship between weight status, determined by the BMI percentile, and dental age and cervical bone maturity.…”
Section: Introductionmentioning
confidence: 99%